Methodological proposal for functional training for schools after gaps of a systematic review (Research, Society and Development, 2022)
Functional training (TF) is a set of movements that work several physical or biomotor skills simultaneously, that is, at the same time. As a result of this integrated development of physical capabilities, the individual is more efficient in activities of daily living and also has an improvement in general physical fitness and sports. This systematic review (SR) study searched the PUBMED database for articles of TF intervention proposals for schoolchildren. At the end of the SR, only 5 studies were found with some characteristics and proposals for intervention in TF for children aged 6-12 years during the school period. The results of these studies showed that TF has numerous benefits in terms of physical fitness, body composition and also in increasing student motivation, compared to the traditional method of Physical Education classes. Due to this lack of studies in the literature on TF for children, this study also proposes a functional training booklet, based on adapted movements of superheroes such as Spider Man, Hulk and Wonder Woman. Therefore, it was concluded that it is possible to create new methodological proposals for PE teaching based on the little available literature and that more investigations are needed about FT for schoolchildren, motivating PE teachers to create new FT proposals that encompass the superheroes or even other essential elements to awaken motivation and participation of practitioners.